2016
DOI: 10.1371/journal.pone.0159343
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Single Locus Single Trait, Multi-Locus and Multi-Trait Association Mapping for Some Important Agronomic Traits in Common Wheat (T. aestivum L.)

Abstract: Genome wide association study (GWAS) was conducted for 14 agronomic traits in wheat following widely used single locus single trait (SLST) approach, and two recent approaches viz. multi locus mixed model (MLMM), and multi-trait mixed model (MTMM). Association panel consisted of 230 diverse Indian bread wheat cultivars (released during 1910–2006 for commercial cultivation in different agro-climatic regions in India). Three years phenotypic data for 14 traits and genotyping data for 250 SSR markers (distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 77 publications
1
41
0
Order By: Relevance
“…Confounding epistatic effects in models suggested that inheritance of these traits is complex and polygenic. Epistasis has been reported for many traits in a number of crops: barley ; maize (Li et al 2016); rice (Matsubara et al 2015), and wheat (Jaiswal et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Confounding epistatic effects in models suggested that inheritance of these traits is complex and polygenic. Epistasis has been reported for many traits in a number of crops: barley ; maize (Li et al 2016); rice (Matsubara et al 2015), and wheat (Jaiswal et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Epistasis effects involved in the models proved that genetic of these traits is complex and polygenic (Lander and Schork 1994 ; Lefebvre and Palloix 1996 ; Hermisson et al 2003 ; Crow 2010 ). Epistasis has been demonstrated for numerous features in a number of cultivars of following species: barley (Kularia and Sharma 2005 ; Bocianowski et al 2016 ), corn (Melchinger et al 1987 ; Li et al 2016 ), sugar beet (Abbasi et al 2015 ), rice (Matsubara et al 2015 ), oilseed rape (Bocianowski et al 2017 ), common wheat (Bnejdi and El Gazzah 2008 ; Jaiswal et al 2016 ), and sorghum (Finkner et al 1981 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past ten years, several GWAS approaches have been used to identify signi cant SNPs, especially evaluating agronomic traits in common wheat (T. aestivum L.) traits using a single locus and two multi-locus approaches [75]. Conclusively, V Jaiswal, V Gahlaut, PK Meher, RR Mir, JP Jaiswal, AR Rao, HS Balyan and PK Gupta [75] veri ed that ML-GWAS has more detection power than SL-GWAS by revealing ten Marker Trait Associations (MTAs) through SL-GWAS while, 22 MTAs through multi locus mixed model (MLMM) and 58 MTAs through multi-trait mixed model (MTMM). A more recent study of Ward and his co-researchers utilized a conventional mixed linear model and recently developed FarmCPU approach to dissect the genetic architecture of yield related traits in winter wheat.…”
Section: Signi Cance Of Gwas Using High-density Genotypingmentioning
confidence: 99%